Cholangiojejunostomy assisted by techniques of interventional radiology for a patient with recurrent jaundice after Kasai portoenterostomy - Ryuji Okubo; Hideyuki Sasaki; Hideki Ota; Motoshi Wada; Taichi Fukuzawa; Hironori Kudo; Ryo Ando; Yuki Endo; Masatoshi Hashimoto; Kosuke Sato; Kei Takase; Masaki Nio (Elsevier, 2021)
A 10-month-old girl who had previously undergone Kasai portoenterostomy (KP) for biliary atresia was admitted because of recurrent jaundice. Intrahepatic bile duct (IHBD) dilation was observed in the lateral segment close to the umbilical portion of the portal vein on ultrasonography and computed tomography. Although percutaneous transhepatic biliary drainage by a radiologist alleviated jaundice, internal fistula formation, which was subsequently attempted, was unsuccessful due to the narrow and complicated IHBD morphology. Therefore, side-to-side cholangiojejunostomy between the dilated IHBD and jejunum of the Roux-en-Y limb was performed using intraoperative interventional radiology techniques. The patient's postoperative course was uneventful. In patients with recurrent jaundice after KP, especially that associated with solitary IHBD dilatation, a high success rate of achieving good bile flow can be expected using current techniques.